A Medical Student Initiative to Enhance the Pediatric Hemodialysis Experience - Stephanie S. Camhi; Olivia Neumann; Jayanthi Chandar (SLACK Incorporated, 2021)
Background: Children and young adults receiving hemodialysis (HD) face unique challenges including frequent school absenteeism, psychosocial issues, and social isolation, placing them at risk for decreased academic achievement and health literacy. Objective: To address this, we implemented the Child and Adolescent Motivation and Enrichment Program (CHAMP) at Holtz Children's Hospital in Miami, FL. The objective of this study is to describe the organizational structure and program design of CHAMP and provide preliminary program opinions. Methods: Medical students served as longitudinal one-on-one mentors to patients receiving HD. Face-to-face intervention, books, board games, and electronic tablets were used to enhance patients' educational and recreational experience. We surveyed participating patients, medical students, and unit nurses regarding their opinions of CHAMP. Key Results: Patients responded to a series of questions on a Likert scale scored from 1 to 5 and reported the highest scores on questions pertaining to having fun with mentors (mean = 4.88), enjoying mentor visits (mean = 4.78), and learning during visits (mean = 3.88). Mentors reported the highest level of agreement (mean = 4.82) that CHAMP helped them gain empathy for patients with chronic and/or special health care needs. Nurses scored highly on the point that "overall, the program was useful and helped the patient" (mean = 6.86 of a possible 7). Conclusion: CHAMP is an academic and psychosocial enrichment program for children and adolescents receiving HD. The program is regarded highly by participating patients, medical students, and unit nurses. Patients report enjoying and learning from mentor sessions, whereas nurses report improved interactions with patients. Medical students who participate as mentors also gain important exposure to the field of pediatric nephrology. The program design as described herein positions CHAMP for replication at academic medical centers nationwide, allowing for optimization of the health and well-being of the pediatric HD population.